Phagocytic ability declines with age in adult Drosophila hemocytes. Issue 4 (14th May 2014) - Horn, Lucas; Leips, Jeff; Starz‐Gaiano, Michelle
Summary Most multicellular organisms show a physiological decline in immune function with age. However, little is known about the mechanisms underlying these changes. We examined Drosophila melanogaster, an important model for identifying genes affecting innate immunity and senescence, to explore the role of phagocytosis in age‐related immune dysfunction. We characterized the localized response of immune cells at the dorsal vessel to bacterial infection in 1‐week‐ and 5‐week‐old flies. We developed a quantitative phagocytosis assay for adult Drosophila and utilized this to characterize the effect of age on phagocytosis in transgenic and natural variant lines. We showed that genes necessary for bacterial engulfment in other contexts are also required in adult flies. We found that blood cells from young and old flies initially engulf bacteria equally well, while cells from older flies accumulate phagocytic vesicles and thus are less capable of destroying pathogens. Our results have broad implications for understanding how the breakdown in cellular processes influences immune function with age.